Stem Cell Differentiation: Electrical Differentiation of Mesenchymal Stem Cells into Schwann‐Cell‐Like Phenotypes Using Inkjet‐Printed Graphene Circuits (Adv. Healthcare Mater. 7/2017). Issue 7 (April 2017) - Das, Suprem R.; Uz, Metin; Ding, Shaowei; Lentner, Matthew T.; Hondred, John A.; Cargill, Allison A.; Sakaguchi, Donald S.; Mallapragada, Surya; Claussen, Jonathan C.
Abstract : Jonathan C. Claussen, Surya Mallapragada, Donald S. Sakaguchi, and co‐workers demonstrate how the application of electrical stimuli via an inkjet printed graphene electrode can induce the differentiation of mesenchymal stem cells (MSCs) into Schwann cell (SC)‐like phenotypes in article number 1601087. This thin and flexible graphene‐based electrode could potentially be used as an implantable neural interface material for peripheral nerve regeneration.